Antibacterial Activity of Two Flavans from the Stem Bark of Embelia schimperi - Babe Guyasa; Yadessa Melaku; Milkyas Endale (Advances in Pharmacological Sciences)
Embelia schemperi Vatke is one of the medicinal plants used traditionally for treatment of intestinal tape worm, dysmenorrheal, bacterial, and fungal infections. Phytochemical screening test of the dichloromethane/methanol (1 : 1) and methanol extracts revealed the presence of phenols, alkaloids, tannins, and flavonoids whereas terpenoids, glycoside, and phytosterols were absent. Silica gel column chromatographic separation of the methanol extract afforded 3,5,7,3′,4′-pentahydroxyflavan, named epicatechin (1), along with a close flavan derivative (2). Structures of the compounds were elucidated by spectroscopic techniques (1D and 2D NMR, FTIR, and UV-Vis). The crude extracts and isolated compounds were screened for in vitro antibacterial activity against strains of Klebsiella pneumoniae, Escherichia coli, Cryptococcus neoformans, Shigella dysentriae, and Staphylococcus aureus. Epicatechin (1) exhibited comparable antibacterial activity against S. aureus and E. coli (15 and 12 mm zone of inhibition, resp.) to that of the control antibiotic gentamicin, with zone of inhibition of 15 and 12 mm, respectively, at a concentration of 20 µg/mL.